0.22y-0.6=0.12y+0.7y

Simple and best practice solution for 0.22y-0.6=0.12y+0.7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.22y-0.6=0.12y+0.7y equation:


Simplifying
0.22y + -0.6 = 0.12y + 0.7y

Reorder the terms:
-0.6 + 0.22y = 0.12y + 0.7y

Combine like terms: 0.12y + 0.7y = 0.82y
-0.6 + 0.22y = 0.82y

Solving
-0.6 + 0.22y = 0.82y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.82y' to each side of the equation.
-0.6 + 0.22y + -0.82y = 0.82y + -0.82y

Combine like terms: 0.22y + -0.82y = -0.6y
-0.6 + -0.6y = 0.82y + -0.82y

Combine like terms: 0.82y + -0.82y = 0.00
-0.6 + -0.6y = 0.00

Add '0.6' to each side of the equation.
-0.6 + 0.6 + -0.6y = 0.00 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + -0.6y = 0.00 + 0.6
-0.6y = 0.00 + 0.6

Combine like terms: 0.00 + 0.6 = 0.6
-0.6y = 0.6

Divide each side by '-0.6'.
y = -1

Simplifying
y = -1

See similar equations:

| 2p-22=18+7p | | -2x-11=6x+21 | | 9x-27=4-8x | | 20=y-10 | | 23r=-161 | | 6x-19=-61 | | 2x+2x-4+4x=76 | | -2-(-15)= | | -7t^2-3t+7=0 | | 2(ax+b)+3=x | | -5j^2+2j+5=0 | | 10-1x=20+5x | | 13x+5=50 | | 6y^2-7=0 | | y=-4(x-3) | | y=-4x(x-3)(x+2)(2x-1) | | 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 | | (3c-7)(2c-5)= | | 2m+6n+4m+8n= | | 37-29=4 | | 2x-4=2(5+x) | | -80+360= | | =12+6(8m-3) | | (90)(-4)= | | 4yx^4*2x^2y^5=0 |

Equations solver categories